Demographic and Clinical Findings of Epilepsy Patients who Underwent Follow-up at the Newly Established Clinic of the Muğla Sıtkı Koçman University Faculty of Medicine - Yasemin ÜNAL; Dilek ASLAN ÖZTÜRK; Mustafa YILMAZ; Gülnihal KUTLU (Archives of Epilepsy, 2016)

(untitled)
Objectives:The aim of the present study was to evaluate demographic and clinical findings of patients who underwent follow-up at the newly established epilepsy outpatient clinic of the Muğla University Faculty of Medicine.Methods:Included were 208 patients who underwent follow-up at the clinic between March 2014 and September 2015.Results:Mean age was 29.42±15.86, with a range of 5–84 years. Eighty-three patients were men (39.9%); 125 were women (60.1%). The most common risk factors included head trauma, febrile convulsion, and family history of epilepsy. Seizures of 155 patients (75.5%) were partialonset, those of 22 (10.6%) were generalized, and those of 9 (4.3%) were unclassified. Sixty-seven patients (37.2%) had normal electroencephalogram, 96 patients (53.3%) had partial, and 10 patients (5.6%) had generalized epileptiform abnormalities. Of the 172 patients (28.5%) to whom antiepileptic drugs had been administered, 49 were resistant to medical treatment. Of the patients with modified therapy, 22 (41.5%) were seizure-free, 7 (13.2%) experienced >50% reduction in seizure frequency, and 8 experienced <50% reduction. Seizure frequency of 16 patients (30.2%) did not change.Conclusion:Regular monitoring of patients in certain centers significantly increases compliance, success of treatment, seizure-free rate, and the monitoring of side effects.